Endoscopic Management of Pediatric Foreign Body Ingestions and Food Bolus Impactions: A Retrospective Study from a Tertiary Care Center - Shafiq, Syed; Devarbhavi, Harshad (Journal of Digestive Endoscopy, 2023)
Background Foreign body (FB) ingestion is a common pediatric problem with the majority of these occurring in children younger than 3 years. Management varies depending on the age of the patient, ingested object(s), its location along the digestive tract, and the available expertise. We aim to report our experience with endoscopic management of FB ingestions in children (<18 years).Materials and Methods We retrospectively reviewed and analyzed endoscopic and medical records from our hospital database of all pediatric patients (<18 years) who presented with FB ingestion between January 2011 and December 2021.Results Our analysis included a total of 368 patients. FB ingestions and/or food bolus impactions were noted in 242 and 11 children, respectively while 115 (31.25%) had spontaneously passed off FB from the digestive tract. Most common FB was coin (28.5%) followed by animal bones (26.2%). Endoscopic management of FBs and food bolus impaction was successful in 247 children (97.63%), while endoscopic FB retrieval failed in 6 children including 1 with fish bone and 5 with button batteries. A total of 9 out of 11 children with food bolus impaction had underlying esophageal pathology, the commonest being corrosive stricture (n = 7). No mortality related to endoscopic intervention was reported.Conclusions Endoscopic retrieval of ingested FBs and food bolus impaction in children is a safe and effective approach when performed by experienced endoscopists and is associated with a high success rate and a lower incidence of complications with reduced hospital stay.
Keywords: button battery; coin; fish bone; food bolus; foreign body; stricture